402 A wireless patch-based polysomnography system for sleep studies: effect of the 2016 AASM rules on AHI in normal individuals. (3rd May 2021) - de Vries, Jantina; Rossi, Alessandro; De Francisco, Ruben; Adnane, Soukaina; Schneider, Hartmut; Andries, Daniela
Abstract: Introduction: Current home sleep test (HST) devices are limited by an absence of EEG, or by being too cumbersome to use. We developed a wireless PSG system (Onera Health, NL) consisting of four disposable patches to record EEG, EOG, EMG, SaO2, ECG, bioimpedance derived respiratory airflow and effort, airflow via nasal cannula, snoring sounds, body position, actigraphy, and leg movements. Signals are stored on reusable electronic modules attached to each patch. Methods: We measured PSG hook-up time in 15 healthy laypersons (6 male, 9 female, age 18-to-70 yrs, BMI 29.7±5.2 kg/m2). We also enrolled 6 additional asymptomatic healthy volunteers (2 male, 4 female, age 27-to-33 yrs, BMI 24.3±5.7 kg/m2) with history of occasional snoring, on which we scored the apnea-hypopnea index (AHI) using data from our patch-based PSG system recorded at home. We evaluated scoring using the 2016 AASM rules for hypopneas in comparison to the 2007 AASM rules requiring a greater than 3% fall in SaO2 for obstructive hypopneas. Results: Mean hook-up time for applying all four patches and electronic modules was 4:42 ± 1:20 min. Mean home sleep efficiency was 89.5 SE 1.9% with an average REM% of 20 SE 6.7%. When comparing the 2016 vs 2007 AASM rules for scoring hypopneas, the AHI increased more than threefold during NREM (9.0 SE 2.0/h vs 2.7 SE 0.8/h; p<0.03) and minimally during REM (11.7 SE 2.3/h and 7.1/h SE 1.8/h; p<0.01), implying an overall increase in the AHI from 3.7 SE 0.8/h to 9.9 SE 1.9/h; p<0.02. One subject changed AHI category from normal to mild (3.6 to 14.4/h), another from mild to moderate (12.7 to 26.3/h) using the 2016 AASM rules. Conclusion: Our wireless patch-based PSG system is an easy solution for sleep studies at home or in the sleep lab, lowering the burden to conduct large scale epidemiologic sleep studies. The presence of standard EEG signals allows to determine NREM and REM statistics, respiratory and non-respiratory arousal indices, AHI and RERA's by sleep stages. Preliminary study results show that using cortical arousal criteria for hypopneas, the AHI increase is more pronounced in NREM compared to REM sleep. Support (if any):